The penal sanction and its incidence in the commission of the crimes of aggravated robbery and aggravated robbery in the district of Tacna, period 2008-2011. - Huillca Zegarra, Ever Cristhiam (2013)
Objetive: The present research was conducted in order to  determine the incidence of determining the application of  criminal sanctions in offenses of aggravated robbery and  aggravated robbery in the district of Tacna.  Method: This established the following hypothesis: In  Tacna district applying criminal sanctions may  significantly influence the offenses of aggravated robbery  and aggravated robbery. The research is a form of applied  research, is also a kind of Socio Legal Research that  examines the events and social relations regulated by legal  rules and that is to determine the incidence of criminal  punishment for the crimes of aggravated robbery and  aggravated robbery in the district of Tacna. For this  purpose we considered the information obtained through  the questionnaire, document analysis, and the Certificate  of Interview.  Result: After the phase of analysis and interpretation of  results determined the incidence of the application of  criminal sanctions in offenses of aggravated robbery and  aggravated robbery in the district of Tacna.  Conclusions: The criminal penalties for crimes of  aggravated robbery and aggravated robbery are  inadequately enforced in the district of Tacna.